Variation in macrominerals and trace elements in cows' retail milk and implications for consumers nutrition. (30th August 2023) - Newton, Eric E.; Pétursdóttir, Ásta H.; Beauclercq, Stephane; Clarke, James; Desnica, Natasa; Stergiadis, Sokratis
Graphical abstract: Highlights: When compared with conventional and organic retail milk, Channel Island milk had higher concentrations of Ca, Mg, P, Cu, Mn, Zn and lower concentrations of K. When compared to Channel Island and conventional milk, organic milk had higher concentrations of Mo and lower concentrations of Fe. Milk from typical grazing months had lower concentrations of trace elements than milk from indoor housing months. Variation in milk Ca, P, I and Zn concentrations due to production system and season, can considerably affect their supply to specific consumer demographics. Abstract: Based on previous farm-level studies, this study hypothesised that production system (conventional, CON; organic, ORG; channel island, CHA) and season would cause variation in the concentrations of macrominerals and trace elements in retail milk. On average, milk retained its status as an excellent source of Ca, P, I, and Mo across different demographics, and a very good source of K, Mg, and Zn for children. Compared with CON and ORG, CHA milk contained higher concentrations of Ca, Mg, P, Cu, Mn, and Zn; and lower concentrations of K and I. Macrominerals did not show a clear seasonal pattern but trace elements were all at lower concentrations during the typical grazing season. Variation in mineral concentrations can have implications to Ca and P supply in children, and I and Zn supply across different consumer demographics; while the seasonal variation was more pronounced than that associated with production system.